Simplify each term.

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>28</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>12</mn><mi>x</mi></mstyle></math> from both sides of the equation.

Combine the opposite terms in <math><mstyle displaystyle="true"><mn>12</mn><mi>x</mi><mo>+</mo><mn>23</mn><mo>-</mo><mn>12</mn><mi>x</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>12</mn><mi>x</mi></mstyle></math> from <math><mstyle displaystyle="true"><mn>12</mn><mi>x</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>23</mn></mstyle></math> .

Since <math><mstyle displaystyle="true"><mn>23</mn><mo>≠</mo><mn>8</mn></mstyle></math> , there are no solutions.

No solution

Do you know how to Solve for x 4(3x+7)-5=12x+8? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.